2013
DOI: 10.1053/j.ajkd.2013.02.370
|View full text |Cite
|
Sign up to set email alerts
|

C3 Glomerulonephritis Associated With Monoclonal Gammopathy: A Case Series

Abstract: Background C3 Glomerulonephritis (C3GN) is a proliferative glomerulonephritis resulting from glomerular deposition of complement factors due to dysregulation of the alternative pathway of complement. The dysregulation of the alternative pathway of complement may occur as a result of mutations or functional inhibition of complement regulating proteins. Functional inhibition of the complement regulating proteins may result from a monoclonal gammopathy. Study Design Case series Setting and Participants 32 May… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
160
3
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(171 citation statements)
references
References 31 publications
5
160
3
3
Order By: Relevance
“…Also, the exact trigger of AP dysregulation is unidentified. Some authors are seeking the answer in the frequent prevalence of monoclonal Ig deposition along with C3 and high frequency of plasma monoclonal Ig in C3G patients (approximately 31% of cases diagnosed with C3GN and 71% of DDD cases) [93,94]. An assumption that monoclonal Ig acts as autoantibody activating the AP has been made [82,83].…”
Section: Clinical Features Of C3gn and Dddmentioning
confidence: 99%
“…Also, the exact trigger of AP dysregulation is unidentified. Some authors are seeking the answer in the frequent prevalence of monoclonal Ig deposition along with C3 and high frequency of plasma monoclonal Ig in C3G patients (approximately 31% of cases diagnosed with C3GN and 71% of DDD cases) [93,94]. An assumption that monoclonal Ig acts as autoantibody activating the AP has been made [82,83].…”
Section: Clinical Features Of C3gn and Dddmentioning
confidence: 99%
“…This topic is discussed in greater detail elsewhere in this issue. Direct evidence implicating the monoclonal gammopathy as a cause is lacking in most patients (27,28,30). Rather, the association is on the basis of epidemiologic data.…”
Section: C3 Glomerulopathymentioning
confidence: 99%
“…Light-chain casts occasionally have a crystalline structure that fractures during processing of the tissue. The entities that have nonorganized deposits are MIDD (Randall type), PGNMID, and C3 glomerulopathy (including C3GN and dense deposit disease, which have dominant C3 deposits) with MG (29)(30)(31). Of note, recent studies found that about one third of patients with C3GN have C3GN associated with an MG (31).…”
Section: The Role Of Monoclonal Proteins In Kidney Diseasesmentioning
confidence: 99%
“…The entities that have nonorganized deposits are MIDD (Randall type), PGNMID, and C3 glomerulopathy (including C3GN and dense deposit disease, which have dominant C3 deposits) with MG (29)(30)(31). Of note, recent studies found that about one third of patients with C3GN have C3GN associated with an MG (31). Although the Ig is not well seen on standard immunofluorescence performed on frozen tissue, the Ig can be unmasked by pronase digestion of the paraffin-embedded tissue (32).…”
Section: The Role Of Monoclonal Proteins In Kidney Diseasesmentioning
confidence: 99%
See 1 more Smart Citation